Identification of Material Misconceptions in High School Biology Textbooks and Their Relationship with Students' Misconceptions - Rahma Lestari; Zulyusri Zulyusri (Biology Education Department, Faculty of Teacher Training and Education, University of Nahdlatul Wathan Mataram - Indonesia, 2021)
Misconception is a concept that is different from the concept that has been agreed upon by experts. Misconceptions can cause students to understand concepts incorrectly. This study aims to identify misconceptions in high school biology textbooks and their relationship to misconceptions in students. This research is a meta-analysis with a literature review method on data sources in the form of articles in electronic journals. This study examines the results of the analysis of high school biology textbook misconceptions and student misconceptions from 15 relevant articles. Based on the results of this study, it is known that 12 high school biology textbooks have misconceptions with low, medium, and high misconception categories. The misconceptions contained in the textbooks are on average classified in the low to medium category, but there are also textbook misconceptions that are included in the high category. The results of the analysis of students' misconceptions revealed that students experienced misconceptions in the medium to high category of the 14 high school biology materials tested. Three common causes of misconceptions in students are misconceptions in textbooks, misconceptions in teachers, and misconceptions in students' initial concepts. Thus, it can be concluded that misconceptions in textbooks are one of the main causes of students' misconceptions, which results in students understanding the material incorrectly. This is evidenced by the fact that students experience misconceptions, especially on material that has misconceptions in textbooks.